COVID-19 Cases and Factors Associated with 11 Indonesian Provinces, 2021 - Mugi Wahidin; Wawan Ridwan; Doni Lasut; Aan Kurniawan; Yurika Fauzia Wardhani (Faculty of Public Health, Hasanuddin University, Makassar, 2024)
In collaboration with other stakeholders, National Task Force of COVID-19 Control conducted massive detection of the cases, followed by contact tracing. The study aimed to overview COVID-19 cases from 58 districts of 11 provinces in Indonesia and its associated factors. A cross-sectional study design used secondary data from The National Task Force of COVID-19 Control. COVID-19 cases and other variables were collected in 58 districts in 11 provinces of Indonesia year 2021. The study incorporated descriptive, correlation, and multiple linear regression analysis with the district as an analysis unit. The median of COVID-19 cases was 804 per district, traced cases were 70.6% of cases, cases had contact was 2.6% of cases, close contact was 2,188, the ratio of close contact: cases were 2.75, isolation drop out was 8, quarantine drop out was 9, test for close contact was 962, COVID-19 vaccine dose 1 was 147, dose 2 was 205, and no vaccine was 354. Factors significantly correlated with COVID-19 cases were cases traced, cases have epicontact, close contact, and ratio close contact. In multivariate analysis, the percentage of traced cases, cases had epicontact, isolation drop out, COVID-19 vaccine dose-1, and no COVID-19 vaccine associated with COVID-19 cases. Identifying factors related to the incidence of COVID-19 can be used to increase efforts to prevent and control COVID-19 cases in the community as a response to alertness to the emergence of new cases due to new variation mutations.